Melacak Akar Teori Martabat Tujuh - Wiwi Siti Sajaroh (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2004)
This writing analyzes the roots of the Seven Degrees. Linguistically, “martabat tujuh” translates to seven levels or stages. In terms of terminology, the Seven Degrees is a theory used to explain the occurrence of the universe within the framework of an emanation system. Despite being presented in various forms and versions, the theory is inherently monistic and is based on the same worldview, namely that the visible world flows from the Ultimate Singular. Upon examination, the systematic nature of the Seven Degrees can be traced back to Muhammad Ibnu Fadlillah al-Burhanpuri (d. 1620).